Relationship between parental smoking and adolescent smoking: gender differences and mediation of resilience - Yi Liu; Ling Li; Zhangming Chen; Silan Ren; Ruini He; Yudiao Liang; Youguo Tan; Xu Shao; Shanshan Chen; Xiaogang Chen; Jinsong Tang; Yanhui Liao (BMC Public Health)
Abstract Background Though the relationship between parental smoking and adolescent smoking has been established, gender differences, and mediation of resilience in this relationship are poorly understood. This research aims to investigate the prevalence of adolescent smoking, and to understand how consequences may differ for boys and girls, as well as to explore what role resilience played in this relationship. Methods Through the school-based cross-sectional survey, a total of 65,898 adolescents were involved in this study, and information were collected by self-reported questionnaire. Participants’ smoking status and their parental smoking status were collected by self-made questionnaire, and resilience was assessed by the 10-item Connor-Davidson Resilience Scale (CD-RISC-10). The multivariate logistic regression was conducted to explore the relationship between parental smoking and adolescent smoking. After that, the path analysis was applied to explore the mediation of resilience in this relationship. Results Of all participants, the rate of self-report current smoking and biologically verified smoking was 1.4% and 2.0%, respectively. Both self-reported and biologically verified prevalence of smoking among boys were higher than that in girls. There were gender differences in the impact of parental smoking on adolescent smoking: mother smoking had a negative effect on adolescent smoking, and resilience could mitigate this negative effect. Father smoking had no association with girl smoking, while father smoking was positively associated with boy smoking, and resilience was mediated in this association. Conclusions Our findings suggested smoking prevention in adolescents can be done differently for different genders. Besides, results indicated resilience was important in preventing adolescent smoking. Furthermore, parents quitting smoking can play an important role in preventing adolescent smoking to a certain extent.